2005
DOI: 10.1108/03074800510623092
|View full text |Cite
|
Sign up to set email alerts
|

Organising e‐journals from the point of view of humanities: a case study at the University of Parma

Abstract: Purpose -Research was carried out at the University of Parma with the purpose to investigate the organisation of e-journal titles from a user viewpoint, in order to find out what influence the approach adopted by the library may have on the use of e-journals and what characteristics the organisation of e-journals should have to enable an easy discovery of resources. Design/methodology/approach -The case study involved students, faculty members and library staff in classics and medieval studies. Research method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…About 13.5% (twenty-six) of academics cited this as a major barrier, 55.4% (107) cited it as a minor barrier, and 31.1% (sixty) indicated that this was not a barrier. These results mirror those of researchers such as Bevilacqua (2005), Salaam and Aderibidge (2010) and Shahmohammadi (2012) who reported that the issue of off-campus accessibility is still a concern, especially in developing country universities. Academics from University A and University B complained about challenges with off-campus access more than those from University C. At University A, 21.8% (fifteen) cited challenges with off-campus access as a major barrier to their use of electronic journals.…”
Section: Accessibility Of Resources Off-campussupporting
confidence: 84%
See 2 more Smart Citations
“…About 13.5% (twenty-six) of academics cited this as a major barrier, 55.4% (107) cited it as a minor barrier, and 31.1% (sixty) indicated that this was not a barrier. These results mirror those of researchers such as Bevilacqua (2005), Salaam and Aderibidge (2010) and Shahmohammadi (2012) who reported that the issue of off-campus accessibility is still a concern, especially in developing country universities. Academics from University A and University B complained about challenges with off-campus access more than those from University C. At University A, 21.8% (fifteen) cited challenges with off-campus access as a major barrier to their use of electronic journals.…”
Section: Accessibility Of Resources Off-campussupporting
confidence: 84%
“…They have been trying to establish why university communities, especially in Africa, have not embraced use of the electronic resources as expected. Findings have varied and have included issues of awareness (Bayugo and Agbeko 2007, Dilek-Kayaoglu 2008, Khan and Ahmad 2009, Salaam and Aderibidge 2010, Shahmohammadi 2012, attitudes and perceptions (De Groote 2008, Salaam and Aderibidge 2010, Tyagi 2012, promotion (Thanuskodi 2011, Vasishta andNavivoti 2011), and facilitating conditions as factors that influence the use of these resources (Ondari-Okemwa 2004, Bevilacqua 2005, Upadhyay and Chakraborty 2008, Salaam and Aderibidge 2010, Shahmohammadi 2012. Among the factors affecting electronic journals usage in universities, the issue of facilitating conditions has been prominent, especially in the context of developing countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A smaller sample is considered enough for generating reliable results in qualitative studies, as compared to the quantitative. Previously, researchers conducted qualitative focus group studies on a sample comprising five respondents (Bevilacqua, 2005;Duncan Adrian St and Durrant, 2015); and seven (Ollé and Borrego, 2010). Moreover, 21 company managers were sampled for the quantitative data collection.…”
Section: Samplementioning
confidence: 99%
“…The researchers from humanities are less inclined to use e‐journals. The main barriers are lack of awareness and less number of journals in the field of humanities (Bevilacqua, 2005). This is being contradicted by Brockman et al (2001) and the British Academy (2005) – their studies reveal that humanities and social science researchers actively used full‐text journals and newspapers, rare books, legal documents, digitized classical and literary texts.…”
Section: Usage Across Disciplinesmentioning
confidence: 99%